2016
DOI: 10.1515/biolog-2016-0161
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic change of the rhizosphere microbial community in response to growth stages of consecutively monocultured Rehmanniae glutinosa

Abstract: Abstract, an important medical plant in China, has distinct regional characteristics. It has long suffered from consecutive monoculture obstacles, resulting in severe reduction of quality and yield. The microbial community is believed to play an important role in the monoculture process. However, there are no reports on how microbial compositions change in response to growth of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Xiong et al [ 28 ] compared microbial communities in suppressive- and conducive-soils associated with Fusarium wilt disease and found that Actinobacteria and Firmicutes were strongly enriched in the suppressive soil in a vanilla long-term continuous cropping system. Yang et al [ 18 ] indicated that some probiotic bacteria belonging to Actinobacteria significantly decreased with the extended monoculture of R. glutinosa . In addition, disease suppression that is induced by bioorganic fertilizer application in Nicotiana tabacum and Persea americana was associated with an increase in multiple beneficial strains such as Actinobacteria , Firmicutes , etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Xiong et al [ 28 ] compared microbial communities in suppressive- and conducive-soils associated with Fusarium wilt disease and found that Actinobacteria and Firmicutes were strongly enriched in the suppressive soil in a vanilla long-term continuous cropping system. Yang et al [ 18 ] indicated that some probiotic bacteria belonging to Actinobacteria significantly decreased with the extended monoculture of R. glutinosa . In addition, disease suppression that is induced by bioorganic fertilizer application in Nicotiana tabacum and Persea americana was associated with an increase in multiple beneficial strains such as Actinobacteria , Firmicutes , etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rhizoplane of plant root systems plays a selective gating role in microbiome recruitment from soil [ 19 ] depending on the root phenotypic traits [ 20 ]. This aspect was not studied in previous studies [ 18 ]. In addition, antagonistic activities of beneficial microbial biomarkers in disease-suppressive soils are still poorly understood [ 18 ].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Using Illumina sequencing of small subunit ribosomal RNA (SSU rRNA) genes, previous studies demonstrated that consecutive monoculture of R. glutinosa altered the microbial community structure in rhizosphere soil, and led to the imbalance of the microbial community [ 8 , 20 ]. However, there exists limited knowledge of the functional attributes of root-associated microbes in the rhizosphere soil of R. glutinosa , and the linkages between the variation of functional genes and the dynamics of microbial community.…”
Section: Introductionmentioning
confidence: 99%